Impact of recyclability on the tensile and Impact properties of coated plastic materials for the automotive and electronic sectors [version 3; peer review: 1 approved, 2 approved with reservations] - Esteban Paredes Barros; Pablo Alberto Acuña Domínguez; Raquel Ledo Bañobre; Vanessa Ventosinos Louzao; Miguel Ángel De Dios Álvarez; Denise García Murias (Open Research Europe)
This research focuses on the study of the tensile modulus and impact resistance) of acrylonitrile-butadiene-styrene (ABS) and its blends with polycarbonate (ABS/PC) including recycled and painted material. A comprehensive assessment was done to determine the impact of reprocessing cycles, remaining coating and their combined effect in the final properties of the recycled polymer. Post-consumer materials are in an already-aged state, lowering their initial properties. Mechanical recycling methods showed that the reprocessing cycles have a higher impact on the mechanical performance than the amount of recycling material content. Also, the material is often coated when they are about to be recycled. The remaining coating impurities play a major role in the recycling process, losing up to 42% of the impact resistance for ABS and 28% for ABS/PC. It was demonstrated that below a 10% of remaining paint, both materials retained is performance as a neat product. Impurities was declared to be the most pernicious element on the recycling process and their elimination must be a priority regarding this objective. These results provide a better knowledge of the recycling effect and can be used to decide the potential recyclability of plastic. The ascribed project of this study (DECOAT) aims to develop efficient systems to remove coatings at the end-of-life of the part, to reduce the damage and promote the use of recycled material in high-tech applications.